Oxidative stress-induced posttranslational modifications of human hemoglobin in erythrocytes - Xiang, Wei; Weisbach, Volker Günter; Sticht, Heinrich; Seebahn, Angela; Bussmann, Julia; Zimmermann, Robert; Becker, Cord-Michael (Archives of Biochemistry and Biophysics, 2013)
Posttranslational modifications (PTMs) have been reported in hemoglobin (Hb) treated with ROS/RNS in cell-free experiments. However, little is known about oxidative PTMs of Hb occurring within the erythrocytes. The aim of this study is to characterize the patterns of Hb PTMs in erythrocytes under oxidative stress. Using mass spectrometry, we investigated specifically methionine/tryptophan oxidation, tyrosine nitration, and the modification via 4-hydroxynonenal (HNE), a product of lipid-peroxidation, on Hb. We demonstrated that the treatment with H(2)O(2)/nitrite induced higher levels of Hb oxidation/nitration in purified Hb preparations than in unpurified hemolysates and erythrocytes, indicating that ROS/RNS are primarily removed by antioxidative mechanisms. We further studied Hb from erythrocytes exposed to ?-irradiation. An irradiation of 30-100 Gy triggered a remarkable increase of intracellular ROS. However, 30 Gy did not induce apparent changes in Hb oxidation/nitration and hemolysis, while Hb oxidation/nitration and hemolysis were significantly enhanced by 100 Gy, suggesting that Hb oxidation/nitration are the consequence of overwhelmed antioxidative mechanisms after oxidative attack and reflect the severity of the oxidative damage of erythrocytes. Although irradiation was known to induce lipid-peroxidation, we could not detect HNE-Hb adducts in irradiated erythrocytes. Analyzing PTM patterns suggests Hb nitration as a more suitable indicator of the oxidative damage of erythrocytes.
EVALuna2:4676